Identification of the elementary structural units of the DNA damage response - Francesco Natale (Nature Portfolio, 2017)
Phosphorylated histone H2AX is an early signalling event of DNA double-strand breaks. Here the authors use super-resolution microscopy and ChIP-seq and identify ‘nano-domains’ – chromatin loops decorated by γH2AX and flanked by CTCF.